Mercury(II) determination in commercial cosmetics and local Thai traditional medicines by flow injection spectrophotometry - K. Prasertboonyai (2018)
Synopsis Objective The proposed method was developed for the enhancement of sensitivity for Hg(II) determination using dithizone by adding SDS in the presence of ascorbic acid in sulphuric acid medium. Method The method was based on the reaction between Hg(II) and 1,5-diphenylthiocarbazone (dithizone), in the presence of sodium dodecyl sulphate (SDS) as an anionic surfactant (to avoid solvent extraction) and ascorbic acid in a slightly acidic medium resulting in a soluble orange coloured Hg(II)-dithizone complex which gave the maximum absorption at 490 nm. No extraction system was required in this method. Result Under the optimum conditions, a linear calibration graph was obtained over the concentration range of 0.05-1.50 μg mL-1. The method was characterized by a limit of detection (LOD, defined as 3σ) and limit of quantification (LOQ, defined as 10σ) of 0.03 and 0.14 μg mL-1, respectively. The relative standard deviations for replicate injection were 1.32 and 0.78% (n = 11) for 0.05 and 0.20 μg mL-1of Hg(II) standard solutions, respectively. The developed method has been satisfactorily applied for Hg(II) determination in commercial cosmetics and local Thai traditional medicines. Results obtained by the proposed method are compared favourably with those analysed by ICP-MS. Conclusion Enhancement of sensitivity and rapidity for Hg(II) assay by FIA could be achieved by adding SDS in ascorbic acid. The method would be useful for routine analysis of Hg(II) in real samples.